Cover Feature: Computational Insights on Periodicity in Bonding and Lewis Acidity and Basicity of the p‐Block Trispyrazolylborate Complexes (Eur. J. Inorg. Chem. 2/2023). Issue 2 (21st December 2022) - Prakash, Rini; Mohamed, Amina; Jemmis, Eluvathingal D.; Venugopal, Ajay
Abstract : The Cover Feature illustrates the p‐block complexes of the scorpionate ligand, hydrotris(pyrazolyl)borate (Tp*). The scorpion in the starry sky symbolizes the constellation representing the Tp* ligand. It is connected to a galaxy of elements belonging to groups 13–15. A detailed computational analysis of these low‐valent p‐block complexes shows a periodic increment in intrinsic Lewis acidity down the group. However, global Lewis acidity measures in terms of FIA and IIA indicate the dependency on the choice of the nucleophiles. This study highlights the potential of the Tp* ligand in stabilizing the reactive low‐valent group 13–15 elements and tuning their Lewis acid‐base properties. We thank Manoj Vasudevan for the artwork. More information can be found in the Research Article by E. D. Jemmis, A. Venugopal and co‐workers .